Plastic Composite Boards from Oil Palm Empty Fruit Bunches (OP-EFB) with Variation of Pressing Temperature: Physical and Mechanical Properties - Pirma, Dio Sandhika; Malrianti, Yefsi; Kasim, Anwar; Syukri, Daimon (Journal of Fibers and Polymer Composites, 2024)
Plastic composite boards are made from OP-EFB (oil palm empty fruit bunches) which function as a filler, while HDPE (high-density polyethylene) plastic is used as a matrix. This study was conducted to analyze the physical and mechanical properties of plastic composite boards from empty palm oil bunches and high-density polyethylene plastic based on the effect of pressing temperature and determine the optimum pressing temperature. The temperature used for pressing were 140 oC, 150 oC, 160 oC, 170 oC, and 180 oC with the addition of coupling agents of MAH (maleic anhydride) and BPO (benzoyl peroxide) initiator. Based on the research that has been carried out, the physical and mechanical properties of the resulting plastic composite board are affected by differences in pressing temperature, with an optimum temperature of 170 oC the results of the testing were density, water absorption, MOR (modulus of rupture) compressive strength parallel to the surface and compressive strength perpendicular to the surface were 0.950 g/cm3, 0.090 %, 134.40 kg/cm², 465.80 kg/cm², and 50.40 kg/cm² respectively and the average test results for all treatments were 0.88 g/cm³, 1.00%, 130.20 kg/cm² and 426.96 kg/cm² respectively. The mechanical physical properties of plastic composites meet SNI 8154-2015 standard on WPC (wood plastic composites), except for MOR and perpendicular compressive constancy of the surface.